2015
DOI: 10.4103/0972-124x.145807
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of hyaluronan 0.8% as an adjunct to scaling and root planing in the treatment of chronic periodontitis: A clinical and microbiological study

Abstract: Background:The purpose of this study was to assess the clinical and microbiological effects of the local and sub-gingival application of a hyaluronan gel on scaling and root planing (SRP) in the treatment of moderate generalized chronic periodontitis.Materials and Methods:In this split mouth study, 72 teeth in 18 patients with generalized chronic periodontitis with moderate severity were chosen for the study. Plaque samples were obtained by paper points at required intervals. Contra-lateral pairs of premolars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 12 publications
4
33
0
1
Order By: Relevance
“…The present study demonstrated a positive effect of subgingival hyaluronan application on dental plaque formation; the test group showed a significant lower mean plaque score as compared to the control group at 1st, 4th and 12th weeks. This is in accordance with studies conducted by Eick et al, 12 Pilloni et al, 13 Polepalle et al, 14 and Sapna et al, 15 who showed reductions in PI scores in patients with topical and intrasulcular hyaluronan gel application. Jentsch et al 5 suggested a beneficial effect of hyaluronan gel during the therapy of plaque-induced gingivitis proven by clinical and paraclinical variables.…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated a positive effect of subgingival hyaluronan application on dental plaque formation; the test group showed a significant lower mean plaque score as compared to the control group at 1st, 4th and 12th weeks. This is in accordance with studies conducted by Eick et al, 12 Pilloni et al, 13 Polepalle et al, 14 and Sapna et al, 15 who showed reductions in PI scores in patients with topical and intrasulcular hyaluronan gel application. Jentsch et al 5 suggested a beneficial effect of hyaluronan gel during the therapy of plaque-induced gingivitis proven by clinical and paraclinical variables.…”
Section: Discussionsupporting
confidence: 92%
“…Even in studies wherein the modes of application of HA gel and the frequency differed in the treatment of chronic periodontitis patients, significant reductions in pocket depths were observed. [ 28 31 32 33 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…They, however, did not find a statistically significant difference between the test and control groups. [ 13 27 28 31 34 35 ] This could be attributed to the vast difference in the study design such as the severity of the disease in the subjects, the concentration of the gel, and the mode of application, frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Subgingival application of HA after full mouth SRP in chronic periodontis had beneficial effect observed, in several clinical studies, with overall improvements of periodontal tissues health [36]. Statistically significant reduction of BOP and PD, as compared to control was observed by Johannsen and co-workers, Polepalle and coworkers [46] and Al-Shammari and co-workers [47], after professional subgingival application of 0.8% HA gel, on patients with chronic periodontitis. Similar results were obtained by Rajan et al [48], Sahayata et al…”
Section: Biological Actionsmentioning
confidence: 92%